2005
DOI: 10.1091/mbc.e04-08-0687
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-induced Endocytosis of CC Chemokine Receptor 5 Is Clathrin Dependent

Abstract: The signaling activity of several chemokine receptors, including CC chemokine receptor 5 (CCR5), is in part controlled by their internalization, recycling, and/or degradation. For CCR5, agonists such as the chemokine CCL5 induce internalization into early endosomes containing the transferrin receptor, a marker for clathrin-dependent endocytosis, but it has been suggested that CCR5 may also follow clathrin-independent routes of internalization. Here, we present a detailed analysis of the role of clathrin in che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
100
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(112 citation statements)
references
References 81 publications
(137 reference statements)
12
100
0
Order By: Relevance
“…However, in some cell types, one pathway may play a more dominant role over the other in mediating internalization of the receptor. For example, in chinese hampster ovary (CHO) and mink lung endothelial cells, CCR5 internalizes mainly through the clathrin-dependent pathway [5], while in primary T cells or HEK293 cells, CCR5 predominantly internalizes through caveoli [3]. The result is that receptors undergo a much faster receptor internalization in CHO and mink lung endothelial cells than those in primary T cells and HEK293 cells [3,5].…”
Section: Cell Type Specificitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, in some cell types, one pathway may play a more dominant role over the other in mediating internalization of the receptor. For example, in chinese hampster ovary (CHO) and mink lung endothelial cells, CCR5 internalizes mainly through the clathrin-dependent pathway [5], while in primary T cells or HEK293 cells, CCR5 predominantly internalizes through caveoli [3]. The result is that receptors undergo a much faster receptor internalization in CHO and mink lung endothelial cells than those in primary T cells and HEK293 cells [3,5].…”
Section: Cell Type Specificitymentioning
confidence: 99%
“…Venkatesan et al report that CCR5 is internalized to vesicles that partially colocalized with endogenous caveolin [3], but Signoret et al conclude that CCR5 endocytosis was completely independent of caveolae [5]. The mechanism by which CCR5 internalizes is controversial and needs to be investigated further.…”
Section: Introductionmentioning
confidence: 99%
“…These adaptive mechanisms (active in many G-protein coupled receptors [GPCRs]) operate within different time frames after ligand-receptor interactions [8][9][10][11]. Processes underlying GPCR modulation include ligand-induced internalization, with subsequent recycling or degradation.…”
Section: Introductionmentioning
confidence: 99%
“…β-arrestins also serve as adaptor proteins that link phosphorylated CCR5 to clathrin in order to mediate receptor internalization via endocytosis [8,9,11,13]. Arrestins can additionally act as adaptors in signaling processes [14].…”
Section: Introductionmentioning
confidence: 99%
“…18 Receptor endocytosis is thought to regulate homologous desensitization or the decrease in cell migration observed at higher ligand concentrations. 42,43 Therefore, we measured the kinetics of internalization for these CCR5 variants, when they were exposed to CCL5. It has been previously reported that exposure to ligand for 60 min allows for the maximum internalization of CCR5, 42 all tested variants showed similar internalization at this time point.…”
Section: Functional Ccr5 Variants H-f Dong Et Almentioning
confidence: 99%